Long‐term exposure to air pollution and incident non‐alcoholic fatty liver disease and cirrhosis: A cohort study. (14th September 2022) - Li, Fu‐Rong; Liao, Jian; Zhu, Bin; Li, Xia; Cheng, Zhiyuan; Jin, Cheng; Mo, Chunbao; Wu, Xianbo; Li, Qian; Liang, Fengchao
Abstract: Background and aims: Epidemiological evidence regarding the association of air pollution with the risk of non‐alcoholic fatty liver disease (NAFLD) is limited. This study was to examine the associations of long‐term exposure to various air pollutants and overall air pollution with risk of incident NAFLD as well as cirrhosis, a major liver‐related morbidity for NAFLD. Methods: Included were 456 687 UK residents. Air pollution data included PM2.5, PM2.5–10, PM10, NO2 and NOx . A weighted air pollution score was also generated from PM10 and NOx . Cox proportional hazard models were employed to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We identified 4978 cases of NAFLD and 1575 cases of incident cirrhosis, over a median follow‐up of 11.9 years. PM2.5, PM10, NO2 and NOx exposures contributed to the excess risk of NAFLD associated with air pollution score; and the corresponding adjusted HRs (95% CI) were 1.10 (1.05, 1.14), 1.14 (1.09, 1.20), 1.19 (1.13, 1.24) and 1.11 (1.07, 1.15), respectively, for each interquartile range increase in the above specific air pollutants. Similar patterns were also indicated for cirrhosis risk. Alcohol consumption was an effect modifier for the association between air pollution score and NAFLD risk, whereas body mass index modified the association for cirrhosis risk. Conclusion: Long‐term exposure to air pollution was associated with risks of NAFLD and cirrhosis among the UK population.